(untitled) (ADMPG Journal, 2020)
This article intends to reflect on the adhesion of the municipalities that conform the metropolitan Lima in Peru to the Interoperability Platform of the State (PIDE). The electronic government, which forms part of the interoperability, is attached to the introduction of the managerial state model. New public management requires that public administration is transparent, privileged social control, and accountability. In this sense, the city must have access to the information necessary for its processing, as it is the main consumer of public services. The study presents one of the suggestions made by the working group on the subject of Government and public decisions, the Master of Government and Public Policy of the Pontifical Catholic University of Peru, followed by the cause and effect relationship. Returns to the regulatory framework to understand the gaps in the decision-making process, which raises the need for interviews with stakeholders. Finally, based on the method of thought design, a prototype is developed to bridge one of the identified gaps, the adherence of public services since the electronic government.